2011
DOI: 10.1007/s12043-011-0132-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurement of effective atomic number of composite materials for Compton effect in the γ-ray region 280–1115 keV by a new method

Abstract: In this paper, we report a new method to determine the effective atomic number, Z eff , of composite materials for Compton effect in the γ -ray region 280-1115 keV based on the theoretically obtained Klein-Nishina scattering cross-sections in the angular range 50 • -100 • as well as a method to experimentally measure differential incoherent (Compton) scattering cross-sections in this angular range. The method was employed to evaluate Z eff for different inorganic compounds containing elements in the range Z = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In a recent experimental work [9][10][11][12] on the determination of the effective atomic number, Z ef f , we have shown that H-, C-, N-and O-based composite materials such as sugars, aminoacids, fatty acids and several polymer samples behave like pure incoherent scatterers. This aspect is corroborated by the more recent works of Taylor [13] and Manohara et al [14].…”
mentioning
confidence: 99%
“…In a recent experimental work [9][10][11][12] on the determination of the effective atomic number, Z ef f , we have shown that H-, C-, N-and O-based composite materials such as sugars, aminoacids, fatty acids and several polymer samples behave like pure incoherent scatterers. This aspect is corroborated by the more recent works of Taylor [13] and Manohara et al [14].…”
mentioning
confidence: 99%
“…In order to verify whether these Z eff values are realizable experimentally, we have taken recourse to a Compton scattering experiment based on which the Z eff values of the samples of interest have been determined [4,25,26]. In this experiment the single differential scattering crosssection (SDCS) values have been measured using three monoenergetic gamma sources.…”
Section: S(q Z)mentioning
confidence: 99%
“…Singh et al [6] de ter mined the ef fec tive atomic num ber of some bi nary al loys us ing mul ti ple scat tering of 662 keV gamma rays and have uti lized the Rayleigh to Compton scat ter ing ra tio for the 145 keV photon en ergy to de ter mine the ef fec tive atomic num ber of Pb-Sn al loys (7). Kumar and Umesh [8] mea sured the ef fec tive atomic num ber of com pos ite ma te ri als for the gamma ray re gion of 280-1115 keV at dif fer ent scat ter ing an gles. Demir and Tursucu [9] in ves ti gated the ef fec tive atomic num ber of FeCr and FeNi bi nary ferro al loys us ing the Ray leigh to Compton scat ter ing ra tio of 59.54 keV pho ton en ergy at a 167° scat ter ing an gle.…”
Section: Introductionmentioning
confidence: 99%